2020
DOI: 10.1177/0960327120958105
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A as a risk factor for allergic rhinitis in children

Abstract: Aim: Bisphenol-A (BPA) is an endocrine disrupting compound and may exacerbate or induce allergic diseases. To the best of our knowledge, there is little evidence regarding the effects of BPA exposure on allergic rhinitis (AR) in children. In the present study, we sought to examine whether exposure to BPA in children is associated with AR. Methods: This study was designed as a case controlled clinical study. 140 children diagnosed as allergic rhinitis and 140 healthy children as control group were recruited. BP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Table 1 exhibits the main characteristics of the 20 studies [ 43 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. All included studies were published in the last 15 years (2008–2023).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 exhibits the main characteristics of the 20 studies [ 43 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. All included studies were published in the last 15 years (2008–2023).…”
Section: Resultsmentioning
confidence: 99%
“…The reporting quality was classified as high in 15 studies (75.0%), while five studies (25.0%) had medium reporting quality [ 62 , 66 , 71 , 72 , 73 ]. The risk of bias was classified as very high in two studies [ 58 , 71 ], high in six studies [ 59 , 62 , 65 , 66 , 70 , 72 ], with some concerns in three studies [ 56 , 61 , 68 ], and low in nine studies [ 43 , 57 , 60 , 62 , 63 , 67 , 69 , 73 , 74 ] ( Figure 2 ). Taken together, the higher concerns were due to confounding, the measurement of the exposure, and missing data, as shown in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Humans are being exposed to the bisphenol A (BPA) through plastic food, beverage containers, thermal receipts, medical devices, canned food, and sealant, with detectable levels occurring in urine worldwide (Harley et al, 2013;Braun and Hauser, 2011;Bushnik et al, 2010). Several human studies have reported BPA exposure is associated with the adverse health outcomes, particularly at young age (Nalbantoglu et al, 2021;Healy et al, 2015;Eng et al, 2013). Since BPA has an endocrinological activity and can mimic the hormones like estrogen, hormone-regulated pathways are disrupted, affecting normal growth and development (Martínez et al, 2020;Ohore and Zhang, 2019).…”
Section: Introductionmentioning
confidence: 99%